On hyperbolic relaxation problems - Yong, Wen-An; Jäger, Willi (Analysis and Numerics for Conservation Laws, 2005)
This report summarizes our works on hyperbolic systems of first-order partial differential equations with source terms. We discuss the introduction of our structural stability and entropy dissipation conditions for initial or initial-boundary value problems. For initial value problems, several systematic results are reviewed. These include the non-existence of (linearly stable) relaxation approximations to non-strongly hyperbolic systems of equations, the justification of the formal zero relaxation limit, the existence of relaxation shock profiles, and the existence of global smooth solutions for balance laws.
Gesehen am 21.08.2018